Advanced Collaborative Emissions Study Auxiliary Findings on 2007-Compliant Diesel Engines: A Comparison With Diesel Exhaust Genotoxicity Effects Prior to 2007. (16th June 2017) - Hallberg, Lance M; Ward, Jonathan B; Wickliffe, Jeffrey K; Ameredes, Bill T
Since its beginning, more than 117 years ago, the compression-ignition engine, or diesel engine, has grown to become a critically important part of industry and transportation. Public concerns over the health effects from diesel emissions have driven the growth of regulatory development, implementation, and technological advances in emission controls. In 2001, the United States Environmental Protection Agency and California Air Resources Board issued new diesel fuel and emission standards for heavy-duty engines. To meet these stringent standards, manufacturers used new emission after-treatment technology, and modified fuel formulations, to bring about reductions in particulate matter and nitrogen oxides within the exhaust. To illustrate the impact of that technological transition, a brief overview of pre-2007 diesel engine exhaust biomarkers of genotoxicity and health-related concerns is provided, to set the context for the results of our research findings, as part of the Advanced Collaborative Emissions Study (ACES), in which the effects of a 2007-compliant diesel engine were examined. In agreement with ACES findings reported in other tissues, we observed a lack of measurable 2007-compliant diesel treatment–associated DNA damage, in lung tissue (comet assay), blood serum (8-hydroxy-2′-deoxyguanosine [8-OHdG] assay), and hippocampus (lipid peroxidation assay), across diesel exhaust exposure levels. A time-dependent assessment of 8-OHdG and lipid peroxidation also suggested no differences in responses across diesel exhaust exposure levels more than 24 months of exposure. These results indicated that the 2007-compliant diesel engine reduced measurable reactive oxygen species–associated tissue derangements and suggested that the 2007 standards–based mitigation approaches were effective.